2020
DOI: 10.1136/bmjdrc-2019-000819
|View full text |Cite
|
Sign up to set email alerts
|

Better HbA1c during the first years after diagnosis of type 1 diabetes is associated with residual C peptide 10 years later

Abstract: ObjectiveTo identify the factors associated with residual C peptide production at least 10 years after diagnosis in children and adolescents with type 1 diabetes.Research design and methods73 children and adolescents (<25 years), born in 1988–2005, diagnosed with type 1 diabetes were included during the 4-year study period (2013–2016). At least 10 years after diagnosis, we measured any remaining C peptide concentration using an ultrasensitive C peptide ELISA (≥1.17 pmol/L). The average hemoglobin A1c (HbA1c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
1
14
0
1
Order By: Relevance
“…However, other studies showed that BMI might be a risk factor for developing T1DM and for accelerating T1DM progression (19)(20)(21). Better HbA1c levels were associated with higher C-peptide concentrations at diagnosis and could predict residual beta cell function and long-term diabetes control after follow-up (22)(23)(24).…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies showed that BMI might be a risk factor for developing T1DM and for accelerating T1DM progression (19)(20)(21). Better HbA1c levels were associated with higher C-peptide concentrations at diagnosis and could predict residual beta cell function and long-term diabetes control after follow-up (22)(23)(24).…”
Section: Discussionmentioning
confidence: 97%
“…A number of previous studies reported that the insulin secreting capacity becomes depleted in T1DM patients soon after diagnosis ( 14 , 15 ), but results from the Joslin Medalist Study showed persistent insulin production in 67.4% of participants at 50 years after diagnosis ( 16 ). Also, several recent studies presented a slow decline of serum C-peptide levels and preservation of the insulin secreting capacity ( 17 19 ). Previously, a preliminary study conducted with a small number of T1DM patients and showed a slight increase in serum C-peptide levels after diagnosis followed by significant decrease 5 years later ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the control group (n = 19), an increased level of antibodies was not revealed. Fasting C-peptide levels were as follows: in group «A» -0.86 ng / ml [0.53; 1.4], «B» -0.65 ng / ml [0.27; 0.98], « B «-0.19 ng / ml [0.17; 0.33],» D «-0.01 ng / ml [0.01; 0.01].…”
Section: оригинальное исследованиеmentioning
confidence: 80%
“…В течение более чем 10-летнего наблюдения за 73 пациентами с ежегодными измерениями уровня С-пептида и HbA 1c выявлено, что определяемые (или остаточные) уровни С-пептида более характерны для лиц женского пола и тех, у кого показатель уровня HbA 1c был ниже в течение первых 3 лет от дебюта СД1 [19]. Подобной взаимосвязи нами отмечено не было, однако в нашем случае это было однократное измерение, а не длительное наблюдение в течение 5-10 лет.…”
Section: обсуждение основного результата исследованияunclassified